Experiences and Perceptions in Dyads about Ostomy Care. Meta-synthesis of Qualitative Studies - Quemba Mesa, Mónica Paola; Diaz Fernández, Jenny Katherine; Vargas Rodríguez, Leidy Yemile; Bautista Plazas, Leila; Pulido Barragán, Sandra Patricia (Investigación y Educación en Enfermería, 2023)
Objective. To understand the experiences and perceptions of care dyads (person and caregiver) when having a permanent discharge ostomy. Methods. Meta-synthesis that followed the ENTREQ standards and was registered in PROSPERO CRD42020221755; It was developed in three phases: (i). Search for studies in academic search engines, with MeSH terms: [(Patients) AND (Ostomy)) AND (Caregivers)], including qualitative primary studies published between 2000 and 2020; (ii). Assessment of the methodological quality with the CORE-Q instrument and the credibility of qualitative findings under the guidelines of the Johanna Briggs Institute; and (iii). Comparative analysis according to the guidelines by Sandelowski and Barroso. Results. The work identified 664 studies; in screening, 35 passed to full-text analysis; 22 to methodological quality evaluation; and 10 to meta-synthesis. The study found 43 qualitative findings that constituted four categories: dyads perform instrumental and emotional care; ambivalent family caregiving feelings and actions; assertive and effective family care; and rejection of bodily changes and sexual dysfunction. These categories constitute the central meta-theme: “The dyads experience a life rupture, which is restored in a sea of ​ambivalent ​emotions and learning; at the same time, affective, instrumental and assertive care is constructed”. Conclusions: People who experience having a permanent discharge ostomy express their rejection to the change in bodily image, alterations in sexual life and as a couple. Caregivers and families are the main source of support by being facilitators in self-care, through relationships of mutuality and reciprocity.